Merdeka-Islamic Learning: Analysis of Merdeka Curriculum ‎Implementation in Islamic Religious Education at Elementary Schools in ‎‎2026‎ - Hasbullah; Hamdan; Abdul Muis; Ahmad Sanusi; Akh Bayu Rifki (eL-HIKMAH: Jurnal Kajian dan Penelitian Pendidikan Islam, 2026)
This study examines the implementation of the Merdeka Curriculum (Kurikulum Merdeka) in Islamic Religious Education (PAI) at the elementary school level in Indonesia in 2026. Employing a qualitative descriptive approach through document analysis, interviews, and classroom observations at selected primary schools, this research investigates how the Merdeka Curriculum's core principles student agency, differentiated learning, and the Pancasila Student Profile are integrated within PAI instruction. The findings reveal that while teachers demonstrate increased creativity and flexibility in lesson design, significant challenges remain, including limited digital literacy among PAI educators, inadequate training, and the tension between standardized religious content and adaptive pedagogy. The study concludes that successful integration requires sustained professional development, contextually responsive teaching materials, and stronger institutional support. This research contributes to the growing discourse on reforming Islamic education within national curriculum policy frameworks.